Effect of 6-Benzylaminopurine (BAP) on Apical Shoot Growth of Ramie (Boehmeria nivea L. Gaud.) Wonosobo Clone In Vitro - Anne Nuraini; Esther Christy Natasya Hutajulu; Asri Peni Wulandari; Pauline Elisabeth; Muhammadiyah Muhammadiyah (School of Life Sciences and Technology, Institut Teknologi Bandung, 2026)
Ramie (Boehmeria nivea L. Gaud.) is considered an important natural fiber crop, particularly due to its profitability. However, its propagation still faces some ultrapractical cases. When typical vegetative styles are used, the number of new shops created is relatively low, which makes large-scale production less effective. To address this conclusion, an in vitro study was conducted on the initial Wonosobo ramie clone. The aim was to determine how different concentrations of 6- benzylaminopurine (BAP) affect apical shoot conformation. Six concentrations of BAP (0, 0.5, 1.0, 1.5, 2.0, and 2.5 ppm) were examined in a completely randomized design with four replications. During the cultivation period, several responses were recorded. The study observed the time for shoot emergence, number of shoots formed, and leaf development across all treatments. The response varied across different concentrations, with certain treatments exhibiting slower shoot formation and lower quantities. The highest shoot accumulation was obtained at 1.5 ppm BAP. These results indicate that BAP is important for stimulating shoot extension, but its concentration must be carefully optimized, as both too low and too high levels are less effective. Based on these findings, BAP with 1.5 ppm is optimal for enhancing in vitro shoot production of ramie.